Monitoring System for Elderly Care with Smartwatch and Smartphone - Rosales, Pablo (2017)
In recent years, mobile devices, such as Smartphones and Smartwatches, have increasingly been used as personal healthcare gadgets. This work presents the development of a monitoring system based on a software application over Android OS for mobile devices. The main goal is to use it as tool for monitoring and tracking elderly people. The proposed application allows to: detect falls to the ground of the users; monitor the heart rate; count the number of steps that the users perform during the day and also track their position on a map. Despite the presence of several cases of possible false positives (e.g. answer a call or sending a message could trigger a wrong detection of fall or increase the steps counters.), the results obtained show that it is possible, by using current mobile devices in the market, to supervise and track the user’s activities.